2021
DOI: 10.1029/2020ms002396
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Arctic Plant Functional Types in a Land Surface Model Using Above‐ and Belowground Field Observations

Abstract: Biomass measurements of arctic plants in the Seward Peninsula were used to develop nine arctic plant functional types in the E3SM Land Model • New plant functional types included mosses, lichens, graminoids, and shrubs of different height classes and leaf habits • Simulations across a gradient of plant communities showed how variations in plant traits and soil depth drive different biomass patterns Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 98 publications
1
27
0
Order By: Relevance
“…One reason for the strong predictive power of vegetation type could be that vegetation types reflect integrative proxies of distinct combinations of environmental conditions that control the SEB, including temperature, topography, soil moisture, and permafrost characteristics [18][19][20]26 . However, it has also been shown that the CAVM classes 20 , upon which our vegetation types are largely based, do differ in SEB-relevant traits and functions such as vegetation height, productivity and albedo 25,42 , and therefore, causal effects of vegetation types can also be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the strong predictive power of vegetation type could be that vegetation types reflect integrative proxies of distinct combinations of environmental conditions that control the SEB, including temperature, topography, soil moisture, and permafrost characteristics [18][19][20]26 . However, it has also been shown that the CAVM classes 20 , upon which our vegetation types are largely based, do differ in SEB-relevant traits and functions such as vegetation height, productivity and albedo 25,42 , and therefore, causal effects of vegetation types can also be expected.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, a quantitative understanding of the importance of vegetation type compared to other drivers of the Arctic SEB is missing 11,15,17 . Land surface components in current Earth system models often represent Arctic vegetation by only a single or few plant functional types (PFTs) 18,19 , despite the notable diversity thereof 20 . Previous observational studies demonstrate that Arctic vegetation types can influence SEB-components, including latent and sensible heat fluxes 11,15,[21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…In climate models, vegetation is represented by plant functional types (PFTs), and their distribution and characteristics, together with water and soil fractions, define the modeled albedo. Arctic tundra vegetation is often characterized by only two PFTs (shrub and grass) (Sulman et al ., 2021), and the plant-light interactions are represented by a simplistic big-leaf model (Bonan et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation is divided into multiple PFTs with independent parameterizations controlling photosynthesis, leaf gas exchange, biomass allocation, and other processes (Sulman et al, 2021). The current PFT configuration of ELM follows CLM5; Lawrence et al (2019), which are based on broad plant groups relevant for global-scale configurations (Wullschleger et al, 2014).…”
Section: The Fixation and Uptake Of Nutrients (Fun) Model (Fun30)mentioning
confidence: 99%